Meninjau Ulang Narasi Besar dalam Buku Sejarah tentang Mohammad Natsir pada Masa Percobaan Demokrasi Indonesia, 1950-1957 - Hafnita Sari Dewi Lubis; Muhammad Ihsan Syahaf Nasution (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
The purpose of this article is to analyse M. Natsir's concept of a state, which, incidentally, was refused by the Indonesian government at the time. The concern is really what M. Natsir's actual role and political actions are in reviewing the grand narrative constructed into most history textbooks about his personality and controversial side. The historical method was used in this research. According to the findings of the study, M. Natsir, as a formulator of the Islamic idea on the basis of the Indonesian state, claims that Pancasila's position in Islam does not clash with Islamic values, and that Pancasila is even in line with the Qur'an. Additionally, he is a pioneer of Islamic education reform and was influential in reviving Indonesia through his famous